Penilaian Kinerja Keuangan PT Telkom Indonesia (Persero) Tbk melalui Rasio Profitabilitas - Movizar, Rully; Amanda Putria (Jurnal Aplikasi Perpajakan, 2025)
This study aims to determine the financial performance of PT Telkom Indonesia (Persero) Tbk for the period 2023-2024 based on profitability ratios. This study uses a descriptive quantitative approach with secondary data obtained from IDX financial reports and the company's official website. The profitability ratios used in this study are Gross Profit Margin (GPM), Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE). The results of this study show that financial performance based on GPM, NPM, ROA, and ROE ratios experienced a downward trend in 2023 and 2024. Furthermore, PT Telkom Indonesia (Persero) Tbk remains in a healthy condition (AA) when assessed from the profitability aspect using a weighted score model, although from an individual aspect, most ratios remain in the very healthy category (AAA).